2018
DOI: 10.1016/j.jocs.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A survey of case studies in production scheduling: Analysis and perspectives

Abstract: The problems of production scheduling and sequencing refer to decision making regarding the designation of jobs to available resources and their subsequent order to optimize pre-defined performance measures. From the early days of research in this area until this last decade, the publication of case studies has been scarce, with their frequency only increasing very recently. This survey aims to highlight practical research and case studies published in the literature in the scheduling area, identifying the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 86 publications
0
47
0
Order By: Relevance
“…For instance, Fuchigami and Rangel (2017) found, in a review regarding case studies in production scheduling, that almost half of the case studies were concerned with solving hybrid flow-shops problems, a machine environment that can describe the flow pattern of stress shops. Furthermore, they found that setup constraints were present in 42% of the cases where specific constraints existed, which is a constraint that is commonly found in hybrid flow-shop environments (Romero-Silva et al, 2016a) and which could create the need for building and implementing a complete schedule.…”
Section: Previous Research Supporting the Proposed Fitmentioning
confidence: 99%
“…For instance, Fuchigami and Rangel (2017) found, in a review regarding case studies in production scheduling, that almost half of the case studies were concerned with solving hybrid flow-shops problems, a machine environment that can describe the flow pattern of stress shops. Furthermore, they found that setup constraints were present in 42% of the cases where specific constraints existed, which is a constraint that is commonly found in hybrid flow-shop environments (Romero-Silva et al, 2016a) and which could create the need for building and implementing a complete schedule.…”
Section: Previous Research Supporting the Proposed Fitmentioning
confidence: 99%
“…The literature distinguishes between different problem variants, and for many problem variants, one or even several surveys have been published, most of them studying the problems through a theoretical lens. Indeed, the literature review carried out by Fuchigami and Rangel (2018), the publication real-life cases on scheduling problems have been scarce, with their frequency only increasing very recently. In addition, according to Allahverdi (2015), more than 90% of the literature on scheduling problems ignores setup times/costs.…”
Section: Scheduling Problemmentioning
confidence: 99%
“…The scheduling of tasks in a production line is not a straightforward problem and, therefore, proposed solutions can be found in the literature [9][10][11][12][13]. Some solutions use artificial intelligence considering multiple restrictions [14,15]. In Ðurasević et al (2016) a genetic algorithm is proposed to schedule tasks in several unrelated machines [16].…”
Section: Introductionmentioning
confidence: 99%